2020
DOI: 10.1002/slct.202001798
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into Selective Sensing of Hazardous Hg2+ and Explosive Picric Acid by Using a Pyrene‐Azine‐Hydroxyquinoline Framework in Differential Media

Abstract: A pyrene-hydroxyquinoline tethered ingeniously designed and developed azine based Schiff base luminophoric system, 2-((Z)-((E)-(pyren-1-ylmethylene)hydrazono)methyl)quinolin-8-ol (PHQ) has been explored as a selective 'TURN ON' chromofluorogenic sensor for hazardous Hg 2 + ions in ethanol/H 2 O (9 : 1,v/v) medium with detection limit of 0.22 μM and binding constant of 1.09 x 10 3 M À 1. The detail scrutiny of mechanism of interaction between PHQ and Hg 2 + is rationalized through various techniques like 1 H NM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Most of these are turn‐off sensing probes [ 7,9,14,25,26,48 ] and have not been applied to analyze PA from environmental samples. [ 5,27 ] The probe 10 has been tested in water and soil samples but its limit of detection is almost double than the present method. Moreover, it is based upon the usage of gold nanoparticles, which is very expensive for day to day real applications.…”
Section: Resultsmentioning
confidence: 97%
“…Most of these are turn‐off sensing probes [ 7,9,14,25,26,48 ] and have not been applied to analyze PA from environmental samples. [ 5,27 ] The probe 10 has been tested in water and soil samples but its limit of detection is almost double than the present method. Moreover, it is based upon the usage of gold nanoparticles, which is very expensive for day to day real applications.…”
Section: Resultsmentioning
confidence: 97%
“…S15 (ESI †) show that the LUMO energy of PA (À3.9 eV) lies between the HOMO and LUMO energies of the probes, which gives access to the electron transfer from the LUMO of NIBBCZ or NIFBCZ in the excited state to that of PA, thereby quenching the luminescence. [54][55][56] Therefore, the PET process from the electron-rich probe to the electron-deficient PA is considered the primary reason for the emission quenching.…”
Section: Resultsmentioning
confidence: 99%
“…Sensor 63 showed LOD of 14.7 nM, and capable to quantify Hg 2+ concentration in real water samples. Tapashree et al [ 92 ] reported a pyrene-hydroxyquinoline conjugated azine based Schiff base 64 ( Figure 21 ) for the selective detection of Hg 2+ in ethanol-H 2 O (9:1 v / v ) medium. The absorption bands of 64 at 240 and 290 nm were enhanced with the appearance of a new band at 450 nm upon addition of Hg 2+ .…”
Section: Chromo-fluorogenic Chemosensorsmentioning
confidence: 99%